Boundary conditions for the European Water Framework Directive in the Ria Formosa lagoon, Portugal (physico-chemical and phytoplankton quality elements) - Loureiro, Sofia (2012)
The dynamics between nutrients, the microplankton assemblage and physical factors were evaluated in the Ria Formosa (S. Portugal) coastal lagoon. Water samples were collected from Ramalhete and Ponte within the lagoon and compared with the conditions at Barra, an oceanic inlet. The two lagoon stations represent the boundary conditions of two different water bodies that have been registered as intercalibration sites for the European Water Framework Directive. Sampling coincided with high and low water conditions, at the summer and winter solstice, and at the spring and autumn equinox between June 2001 and July 2002. Chlorophyll a values, with a maximum of 5.1 mg l 1 during growing season, were lower than those reported for similar systems. The maximal winter values of 5.99 mM for total inorganic nitrogen, 0.53 mM for phosphate, and 6.34 mM for silicate, were also lower than previously reported for this area. Microplankton peaked during the summer solstices of June 2001 and July 2002, with maximal abundances of 12 105 cells l 1 and 7 105 cells l 1 for total microplankton, respectively: these communities were dominated by diatoms. At the autumn and spring equinox (September 2001 and April 2002), the maximal abundances were 4.9 105 cells l 1 and 2.6 105 cells l 1 total microplankton, respectively: these communities were more evenly distributed between diatoms, dinoflagellates, nanoflagellates and ciliates. At the winter solstice (December 2001), the microplankton were at their lowest with a maximal abundance of 1.0 105 cells l 1: these communities were dominated by small organisms, particularly nanoflagellates. The oceanic microplankton community at the Barra inlet was generally less numerous and differed in composition from the lagoonal communities at Ramalhete and Ponte. Multivariate analysis clustered the microplankton assemblage according to season. Changes in the microplankton community were related mainly to variations in temperature, solar radiation and salinity, and to the availability of the reduced forms of nitrogen. The differences between the parameters observed at the entrance of the lagoon during the summer solstice of 2001 and 2002 may be due, respectively, to the colder upwelled water during 2001 and the much warmer water observed in 2002. Nutrient enrichment was possible both from coastal waters and from internal lagoonal processes. Consequent accumulation of biomass may occur in inner regions where water circulation is restricted, which may lead to episodes of water quality degradation. This study does not alter the boundary conditions for Ramalhete and Ponte registered at the European Commission, respectively, as ‘good/moderate’ and ‘high/good’.